Copy Number Variations in the Human Genome - A New Page in Psychiatric Genetics: The Collaborative Project Psychcnvs - Kasimov A.A; Mamurova M.M.; Xusainov E.D.; Primqulov R. R. (Genius Journals, 2023)
Variations in the human genome associated with changes in the copy number of individual fragments have always been an object of close attention of medical geneticists. In the second half of the twentieth century, they were detected using cytogenetic methods. Chromosome aneuploidy, i.e., the actual change in copy number of all genes located on a dropped out or extra chromosome, is known to have critical consequences for the phenotype (the classical example is Down syndrome or trisomy 21).
Keywords: molecular genetics; psychiatry; international projects